Prognostic Significance of Statin Use in Colorectal Cancer. Issue 25 (June 2015) - Ling, Ying; Yang, Li; Huang, Huiqiao; Hu, Xiaohua; Zhao, Cuisong; Huang, Hongyan; Ying, Yanping; Bhatnagar., Namrata
<x xml:space="preserve">Abstract</x> Abstract Statin intake has been reported to reduce the risk of several malignancies beyond its cholesterol-lowering effects. However, little is known regarding the survival benefit of statins for patients with colorectal cancer (CRC). We conducted a systematic literature search of multiple databases for studies published before November 2014, which investigated associations between statin intake and CRC prognosis. Meta-analysis was performed using random-effects model. The primary outcomes of interest were all-cause mortality (ACM) and cancer-specific mortality (CSM). Ten studies involving 76, 851 patients were eligible for this meta-analysis, with 7 studies investigating prediagnosis statin use and 5 studies reporting postdiagnosis statin use. Prediagnosis statin use was associated with reduced ACM (hazard ratio [HR] 0.73, 95% confidence interval [CI] 0.61–0.88, P = 0.001) and CSM (HR 0.80, 95% CI 0.77–0.84, P < 0.001) for patients with CRC. This effect persisted when stratified by tumor site and in studies adjusted by nonsteroidal anti-inflammatory drug use. In addition, postdiagnosis statin use was associated with decreased CSM (HR 0.70, 95% CI 0.60–0.82, P < 0.001). However, we did not note reduced ACM for postdiagnosis statin use (HR 0.93, 95% CI 0.68–1.27, P = 0.639). There appeared to be an association between postdiagnosis statin use and increased ACM in KRAS-mutated CRC. Our findings provide evidence that prediagnosis statin therapy was associated with reduced ACM and CSM in CRC patients; postdiagnosis statin therapy indicated decreased CSM. However, findings may not apply to patients with postdiagnosis statin therapy for ACM. Further studies are warranted to determine the relation between statin dose and duration on CRC survival.